1997
DOI: 10.1021/ma960543m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Monomer Ratio on the Strengthening of Polymer Phase Boundaries by Random Copolymers

Abstract: The fracture toughness Gc of an interface between the immiscible homopolymers polystyrene (PS) and poly(2-vinylpyridine) (PVP) reinforced with random copolymers, dPSf-r-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…However, there exist conflicting results regarding the utility of random copolymers as interfacial modifiers. [11,12,13,25] These results include studies on mixtures of polystyrene (PS) and poly(methyl methacrylate) (PMMA) with random copolymers of PS and PMMA as compatibilizer which show that the random copolymer does not improve the strength of the biphasic interface as well as a block copolymer. [12,13] Alternatively, if the same experiment is completed on mixtures of PS and poly(2-vinyl pyridine) (P2VP) with a PS/P2VP random copolymer, the random copolymer substantially improves the interfacial strength between the two homopolymers [11,25] Additionally, seminal work by Fayt et al [32 -36] showed that addition of tapered (which can also be thought of as a type of random) copolymers of PS and polyethylene(PE) to a blend of PS and PE improved the elongation and ultimate strength of that blend more than the addition of a similar diblock copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exist conflicting results regarding the utility of random copolymers as interfacial modifiers. [11,12,13,25] These results include studies on mixtures of polystyrene (PS) and poly(methyl methacrylate) (PMMA) with random copolymers of PS and PMMA as compatibilizer which show that the random copolymer does not improve the strength of the biphasic interface as well as a block copolymer. [12,13] Alternatively, if the same experiment is completed on mixtures of PS and poly(2-vinyl pyridine) (P2VP) with a PS/P2VP random copolymer, the random copolymer substantially improves the interfacial strength between the two homopolymers [11,25] Additionally, seminal work by Fayt et al [32 -36] showed that addition of tapered (which can also be thought of as a type of random) copolymers of PS and polyethylene(PE) to a blend of PS and PE improved the elongation and ultimate strength of that blend more than the addition of a similar diblock copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, the addition of a compositionally symmetric P(S-ran-2VP) resulted in the greatest increase in G c of the interface and forward elastic recoil spectroscopy showed that this copolymer provided a symmetric interface [15]. In a separate study, investigation of the fractured ADCB beams using forward recoil spectroscopy determined that in a system with multiple interfaces fracture always occurs at the interface with the smallest w i [16].…”
Section: Introductionmentioning
confidence: 89%
“…The wafers were washed three times, using alternate washings of acetone and toluene to remove any organic material from the surface. The wafers were then placed in an ultra-violet ozone oven for 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In practice, random copolymers could be good compatibilizers that are relatively easy to synthesize at low cost. Recently, Dai et al investigated the immiscible blend of polystyrene (PS) and poly(2-vinylpyridine) (PVPy) compatibilized by a random copolymer of deuterated PS and PVPy 5 and a random copolymer of poly(styrene-co-2-vinylpyridine) (STVPh). 18 They found that the long, random copolymers could be remarkably effective in reinforcing the immiscible polymer blend interfaces.…”
Section: Introductionmentioning
confidence: 99%